Telling Our Stories: Narrative and Framing in the Movement for Same-Sex Marriage. - Olsen, Kristine A. (Social Movement Studies, 2014)
Although framing and narrative are both well-documented discursive features of social movements, the difference between them is often overstated; where frames are treated as logical, authoritative, and abstract, the usefulness of narratives is frequently documented in relation to pre-mobilization phases of movement development such as identity and community building. Drawing on an analysis of Connecticut's Judiciary Committee hearings on same-sex marriage, I challenge this distinction and elucidate the relationship between storytelling and framing, showing how narrative is used to make packages of frames cohesive and compelling. In demonstrating how proponents of the legislation deployed narratives and frames simultaneously, this research contributes to scholarship on the function and configuration of discursive strategies for social movements.